2017
DOI: 10.19132/1808-5245230.115-141
|View full text |Cite
|
Sign up to set email alerts
|

Análise das influências intelectuais na produção científica da área de Ciência da Informação: um estudo sobre os bolsistas de produtividade em pesquisa (PQ-CNPq)

Abstract: Resumo: Busca investigar as bases intelectuais dos bolsistas de produtividade em pesquisa do Conselho Nacional de Desenvolvimento Científico e Tecnológico da área de Ciência da Informação por meio das suas citações. Para compor o corpus do estudo, elege a Base Referencial de Artigos de Periódicos em Ciência da Informação, considerando o recorte temporal de 1972 até 2015. Adota como procedimentos metodológicos: (1) identificação dos bolsistas de produtividade em pesquisa da área de Ciência da Informação; (2) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Criteria adapted in the evaluation of proposals, researchers, research projects, and requests for funding these agencies are established by those who hold the highest positions in the Brazilian academic hierarchy [20]. It is public knowledge that these criteria are comparative and deeply affected by complex phenomena, often unconscious and not properly proven [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Criteria adapted in the evaluation of proposals, researchers, research projects, and requests for funding these agencies are established by those who hold the highest positions in the Brazilian academic hierarchy [20]. It is public knowledge that these criteria are comparative and deeply affected by complex phenomena, often unconscious and not properly proven [2].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the capacity to train new human resources for research is one of the ways to feed the scientific production chain of knowledge [2,20], there are scientific initiation programs and postgraduate courses at the masteral and doctorate degrees, where capturing of students often expresses the capacity of orientation of the permanent professors because they represent how attractive and recognized they are in the academic and scientific world to carry out these attributions [14]. When compared with other areas of knowledge, it is observed that there are still insufficient capacities developed in this regard in the permanent professors of physiotherapy [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dahlberg I is the most cited author (53 citations), and Smith B and Fujita MLS have the highest citation average considering the corpus of this research. Bufrem, Silva and Sobral (2017) recognized Dahlberg (1978) as the second most cited author in a similar study.…”
Section: The Intellectual Foundation Of Brazilian Research On Komentioning
confidence: 93%
“…A escolha deste grupo seleto se deve ao fato que o CNPq concede, por meio de edital específico, a bolsa de produtividade em pesquisa para pesquisadores que se destacam em determinadas áreas de conhecimento, valorizando a produção científica, segundo critérios estabelecidos pelos Comitês de Assessoramento do CNPq. As bolsas são distribuídas, segundo alguns autores, aos pesquisadores que constituem a elite da produção científica no país, pois, além de outros critérios, os bolsistas devem dedicar-se ao cumprimento dos propósitos constantes nos projetos de pesquisa, mantendo atividades acadêmicocientíficas, oficialmente vinculadas a instituições de pesquisa e ensino (BUFREM;SOBRAL;CAFÉ et. al., 2011) As bolsas de produtividade em pesquisa são classificadas em 3 níveis: nível 2 (PQ2), nível 1 (PQ1) e nível sênior (PQ-Sr), em que o nível 2 representa o menor nível de excelência e o nível sênior representa o maior nível de excelência.…”
Section: E-issn 1808-5245unclassified